PORTABLE ARCHITECTURE ASPECTS IN THE DESIGN OF EMERGENCY SHELTERS FOR EVACUATION DURING THE ERUPTION OF MOUNT SEMERU - Ledy Fitra Ramadhani; Zuhrotul Mawaddatil Ula; Intan Agustina Pratiwi; Asri Dinapradipta; Sri Nastiti Nugrahani Ekasiwi (Center for Scientific Publication, 2026)
Indonesia’s position along the Ring of Fire renders it highly prone to volcanic eruptions, often causing significant displacement and damage to settlements. These conditions highlight the need for effective emergency shelters. However, static emergency shelter solutions, such as conventional tents, are often inadequate for the dynamic evacuation contexts of volcanic disasters. These shelters are typically difficult to transport, slow to deploy, and dependent on skilled labor, resulting in delayed protection for evacuees. This study aims to develop design criteria for portable emergency shelters by applying the principles of portable architecture—mobility, compactibility, lightweight materials, and ease of assembly—to better support evacuation mobility and post-disaster needs. Employing a qualitative descriptive method, the research integrates contextual analysis of Semeru’s eruption characteristics with theoretical frameworks of portable design. Data were collected through literature review, design document analysis, and secondary disaster data, focusing on evacuation dynamics, environmental conditions, and ergonomic requirements. The findings identify three essential design aspects: rapid deployment, compactness, and transportability. The proposed shelter design incorporates retractable and folding systems allowing rapid assembly by non-expert users within five to ten minutes, compact packaging for efficient storage, and lightweight construction suitable for motorcycle transport. This design improves response speed and reduces logistical dependence during disaster evacuation. The study concludes that integrating portable architectural strategies into emergency shelter design enhances adaptability, responsiveness, and independence of affected communities, providing not only physical protection but also supporting the continuity of mobility and dignity during prolonged displacement.